Trend On Public Administration Research: A Bibliometric Analysis - Ismail Nurdin Nurdin; Sri Hartati; Afriati Afriati (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2022)
This research aims to present publications on Public Administration from the Scopus database using a bibliometric analysis. The Publish or Perish method by Harzing was used for citations in the form of metrics, while Microsoft Excel and VOS viewer were used for frequency analysis and visualization of data between 2010-2021. Findings: Based on the results, the publications on Public Administration have consistently increased since 2015 with 656 citations. The most popular keywords identified are development, drug administration, food and practice, China, impact, review and state, application, research, big data, future and Public Administration, case, evolution, and efficiency.Keywords: Public Administration; Bibliometric Analysis AbstrakPenelitian ini bertujuan untuk menyajikan publikasi tentang Public Administration dari database Scopus dengan menggunakan analisis bibliometrik. Metode penelitian melalui Publish or Perish oleh Harzing digunakan untuk kutipan dalam bentuk metrik, sedangkan Microsoft Excel dan VOS viewer digunakan untuk analisis frekuensi dan visualisasi data antara 2010-2021. Temuan: Berdasarkan hasil, publikasi Administrasi Publik secara konsisten meningkat sejak tahun 2015 dengan 656 kutipan. Kata kunci yang paling populer diidentifikasi adalah pengembangan, administrasi obat, makanan dan praktik, Cina, dampak, tinjauan dan status, aplikasi, penelitian, data besar, masa depan dan Administrasi Publik, kasus, evolusi, dan efisiensi.Kata Kunci: Administrasi Publik; Analisis Bibliometrik